2015
DOI: 10.2174/1871527314666150225144300
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Amino Acids in Migraine Patients without and with Aura and their Possible Usefulness in the Study of Migraine Pathogenesis

Abstract: We found higher level of His in migraine patients without and with aura and lower level of Val and Leu in patients with migraine without aura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, their different pathogeneses have been demonstrated. Domitrz et al (2015) found a higher level of histidine in subjects with migraine without and with aura and a lower level of valine and leucine in subjects with migraine without aura. Higher plasma glutamine and aspartic acid levels have also been found in patients with migraine (notably with aura) between attacks (Ferrari et al, 1990).…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, their different pathogeneses have been demonstrated. Domitrz et al (2015) found a higher level of histidine in subjects with migraine without and with aura and a lower level of valine and leucine in subjects with migraine without aura. Higher plasma glutamine and aspartic acid levels have also been found in patients with migraine (notably with aura) between attacks (Ferrari et al, 1990).…”
Section: Discussionmentioning
confidence: 81%
“…Leucine, isoleucine and valine are branched-chain amino acids (BCAAs), BCAAs have emerged as potential biomarkers of disease as they are associated with risk of cardiovascular disease, end-stage renal failure, and ischemic stroke [ 67 ]. In a small study of 37 migraine patients and 40 controls elevated levels of isoleucine in blood serum were found [ 68 ]. A recent study investigated amine pathways in 20 patients with migraine without aura, and 20 healthy subjects in serum with liquid chromatography coupled to mass spectrometry (LC-MS) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interesting observations were demonstrated in another article [27] based on the previously described research by D' Andrea et al Researchers aimed to verify the hypothesis of a similar pathogenesis of ED to migraine, which suggests catecholamine and trace amine dysregulation in both diseases. Since this has been demonstrated to play a role in migraine [28,29], similar observations in ED would allow better understanding of some consistent mechanisms underlying both disorders. Therefore, plasma levels of dopamine (DA), noradrenaline (NA), tyrosine (Tyr), and octopamine (Oct) were measured in BN and AN patients, and compared to healthy controls.…”
Section: Migraine and Eating Disorders Are Presumably Correlatedmentioning
confidence: 77%